(untitled) (Zoological Records and Reviews, 2024)
Biological invasions rank among the leading drivers of global biodiversity loss, yet the mechanistic pathways through which invasive species alter native community structure – competition, predation, hybridisation, disease transmission, and ecosystem engineering – remain incompletely quantified in multi-species field contexts. This study characterises ecological interactions between four established invasive species – Procyon lotor (raccoon), Trachemys scripta elegans (red-eared slider), Pseudorasbora parva (topmouth gudgeon), and Fallopia japonica (Japanese knotweed, as habitat modifier) – and their native ecological counterparts across 12 freshwater and riparian sites in the Netherlands and Bavaria, Germany (n = 8,614 individual records, 2021-2023). Competitive displacement was quantified by comparing native species occupancy and abundance at invaded versus uninvaded paired sites. Procyon lotor reduced native waterbird nest success by 38.4 +- 6.2% through egg predation (generalised linear mixed model: z = 4.81, p < 0.001). Trachemys scripta elegans competitively displaced Emys orbicularis at 8 of 9 co-occurrence sites, reducing native turtle basking time by 61.3 +- 8.4%. Pseudorasbora parva presence reduced native cyprinid species richness by 2.8 +- 0.6 species per site (t(10) = 4.63, p < 0.001), mediated by both competition for zooplankton resources and rosette virus (Sphaerothecum destruens) transmission. Fallopia japonica invasion reduced riparian ground-dwelling invertebrate richness by 44.2% within invaded patches relative to adjacent uninvaded margins. These findings quantify multi-pathway invasion impacts and inform priority ranking for management interventions under the EU Invasive Alien Species Regulation (EU 1143/2014).